Cleavage of p65/RelA of the NF-κB pathway by Chlamydia - Lad, Sonya P. (National Academy of Sciences, 2007)
Chlamydia trachomatis is a bacterial pathogen that infects the eyes and urogenital tract. Ocular infection by this organism is the leading cause of preventable blindness worldwide. The infection is also a leading cause of sexually transmitted disease in the United States. As obligate intracellular pathogens, chlamydiae have evolved sophisticated, yet undefined, mechanisms to maintain a favorable habitat for intracellular growth while avoiding harm to the host. We show here that chlamydiae have the ability to interfere with the NF-κB pathway of host inflammatory response. We found that Chlamydia infection did not promote IκBα degradation, a prerequisite for NF-κB nuclear translocation/activation, nor induce p65/RelA nuclear redistribution. Instead, it caused p65 cleavage into an N terminus-derived p40 fragment and a p22 of the C terminus. The activity was specific because no protein cleavage or degradation of NF-κB pathway components was detected. Moreover, murine p65 protein was resistant to cleavage by both human and mouse biovars. The chlamydial protein that selectively cleaved p65 was identified as a tail-specific protease (CT441). Importantly, expression of either this protease or the p40 cleavage product could block NF-κB activation. A hallmark of chlamydial STD is its asymptomatic nature, although inflammatory cellular response and chronic inflammation are among the underlying mechanisms. The data presented here demonstrate that chlamydiae have the ability to convert a regulatory molecule of host inflammatory response to a dominant negative inhibitor of the same pathway potentially to minimize inflammation.